Long-term outcome in patients with Guillain-Barré syndrome requiring mechanical ventilation - Witsch, Jens; Galldiks, N.; Bender, A.; Kollmar, R.; Bösel, Julian; Hobohm, C.; Günther, A.; Schirotzek, I.; Fuchs, K.; Jüttler, E. (Journal of neurology, 2013)
We aimed to determine long-term disability and quality of life in patients with Guillain-Barré syndrome (GBS) who required mechanical ventilation (MV) in the acute phase. Our retrospective cohort study included 110 GBS patients admitted to an intensive care unit and requiring MV (01/1999-08/2010) in nine German tertiary academic medical centers. Outcome was determined 1 year or longer after hospital admission using the GBS disability scale, Barthel index (BI), EuroQuol-5D (EQ-5D) and Fatigue Severity Scale. Linear/multivariate regression analysis was used to analyze predicting factors for outcome. Mean time to follow up was 52.6 months. Hospital mortality was 5.5 % and long-term mortality 13.6 %. Overall 53.8 % had a favorable outcome (GBS disability score 0-1) and 73.7 % of survivors had no or mild disability (BI 90-100). In the five dimensions of the EQ-5D “mobility”, “self-care”, “usual activities”, “pain” and “anxiety/depression” no impairments were stated by 50.6, 58.4, 36.4, 36.4 and 50.6 % of patients, respectively. A severe fatigue syndrome was present in 30.4 % of patients. Outcome was statistically significantly correlated with age, type of therapy and number of immunoglobulin courses. In GBS-patients requiring MV in the acute phase in-hospital, and long-term mortality are lower than that in previous studies, while long-term quality of life is compromised in a large fraction of patients, foremost by immobility and chronic pain. Efforts towards improved treatment approaches should address autonomic dysfunction to further reduce hospital mortality while improved rehabilitation concepts might ameliorate long-term disability.